Peran Management Characteristics terhadap Employee Job Satisfaction, Employee Creativity, dan Turnover Intention - Utami, Wika; Lestari, Unik Dwi (Jurnal Maksipreneur, 2025)
The purpose of this study is to investigate the relationship between supervisor humility, abusive supervision, and employee job satisfaction, employee creativity, and turnover intention. This study adds a turnover intention variable, which aims to determine the effect of turnover intention on the level of employees’ job satisfaction, and this research is expected to contribute to increasing the information at the theoretical or scientific level of human resource management, and also has positive managerial implications for increasing employees’ job satisfaction. This study employs a purposive sampling method, drawing on 175 employees from service companies in Jakarta, Indonesia. We used LISREL's factor analysis and structural equation modeling (SEM) methods. The result of this study is that supervisor humility has an indirect positive effect on employees’ creativity. On the other hand, abusive supervision has an indirect negative impact, in which employees’ job satisfaction is mediated by this type of supervision. Meanwhile, employees’ job satisfaction doesn’t have a negative effect on turnover intention, while abusive supervision has a positive effect. In this case, employee job satisfaction does not mediate the relationship between supervisor humility and abusive supervision on turnover intention, because the effect of job satisfaction on turnover intention is also unstable within an organization or company. The Covid-19 pandemic is still ongoing.